EXTENDED DISTRIBUTION OF TWO WOODPECKER SPECIES (Micropternus brachyurus and Picus vittatus) IN MERU BETIRI NATIONAL PARK, EAST JAVA, INDONESIA - Arif Mohammad Siddiq; Puji Firmansyah; Agung Sih Kurnianto; Muhammad Kurniawan; Nur Kholiq; Hari Sulistiyowati (Treubia, 2024)
This study discovered extended distribution of two woodpeckers, i.e., the Rufous Woodpecker (Micropternus brachyurus) and the Laced Woodpecker (Picus vittatus) in Meru Betiri National Park, East Java. The records of M. brachyurus were observed three times in Bandealit Resort (9 December 2021, 12 February 2022, and 20 April 2022) and once in Baban Resort on 9 September 2023. These record areas were around the first record area in secondary forest and the edge of plantations (Albizia, Cocos, and Ochroma) that also bordered the Bandealit road. The second record found a single individual foraging in Mangifera indica. The record of P. vittatus was observed once at Bandealit Resort on 11 February 2024. This species perched on Cocos nucifera, Mangifera indica, and Tectona grandis. Referring to altitude distribution, P. vittatus was only recorded at an altitude of 78 m asl., while M. brachyurus was more variable in the range of 79–651 m asl. These findings provide an essential update for the bird checklist in Meru Betiri National Park, particularly in the last 10 years ago.